2018
DOI: 10.1007/s10897-018-0243-7
|View full text |Cite
|
Sign up to set email alerts
|

Why Patients Decline Genomic Sequencing Studies: Experiences from the CSER Consortium

Abstract: Clinical and research settings are increasingly incorporating genomic sequencing (GS) technologies. Previous research has explored reasons for declining genetic testing and participation in genetic studies; however, there is a dearth of literature regarding why potential participants decline participation in GS research, and if any of these reasons are unique to GS. This knowledge is essential to promote informed decision-making and identify potential barriers to research participation and clinical implementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 31 publications
3
43
0
Order By: Relevance
“…We found that the vulnerability of parents in this setting was clear and parents spoke about doing anything to help their child. They put aside concerns around data sharing and insurance, which are the commonly cited reasons for declining genomic sequencing in other settings [ 28 ]. When reflecting on being offered RGS parents felt the choice was straightforward, they had sufficient information and time to make a decision and none reported regretting their decision, which are all indicators of informed decision making.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the vulnerability of parents in this setting was clear and parents spoke about doing anything to help their child. They put aside concerns around data sharing and insurance, which are the commonly cited reasons for declining genomic sequencing in other settings [ 28 ]. When reflecting on being offered RGS parents felt the choice was straightforward, they had sufficient information and time to make a decision and none reported regretting their decision, which are all indicators of informed decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to participation in genomic research studies include lack of community engagement, mistrust on the part of the patient, logistical barriers, and privacy and discrimination concerns. 31,32 These barriers are likely exacerbated in underserved populations. Additional challenges for genomic medicine implementation research in underserved groups include a lack of diversity in the scientific community, smaller sample sizes, and the analytical challenges faced when studying participants of mixed ancestry.…”
Section: Introductionmentioning
confidence: 99%
“…Since previous reports have described concerns about privacy and discrimination as being potential barriers to participation in genetic research, 25,32,33 we were apprehensive about how placement of genetic results in the EHR might impact recruitment. Interestingly, few potential participants declined when invited in-person, possibly because they had a trusting relationship with the medical team, and few of them reported privacy or discrimination concerns.…”
Section: Discussionmentioning
confidence: 99%